2000
DOI: 10.1002/(sici)1097-0266(200006)21:6<689::aid-smj115>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Ownership structure and economic performance in the largest european companies

Abstract: The paper examines the impact of ownership structure on company economic performance in the largest companies from 12 European nations. Ownership structure is measured by the identity and share of the largest owner. Performance is measured by return on assets, market to book values and sales growth controlling for industry, capital structure and nation effects. We find evidence of a bell-shaped (first increasing and then decreasing) effect of ownership share on assets returns and market-to-book values of equit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
761
1
44

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,006 publications
(885 citation statements)
references
References 72 publications
(115 reference statements)
42
761
1
44
Order By: Relevance
“…Many categories of owner behave differently, according to their interests and preferences (Pederson and Thomsen, 2000 and Thomsen and Pederson, 2003). In emerging economies, owner identity is more important than ownership concentration (Dyck, 2000;Firth et al 2007;Omran et al 2008;Wu et al 2009 andChi and).…”
Section: Divc= Votr1 -Casr1mentioning
confidence: 95%
“…Many categories of owner behave differently, according to their interests and preferences (Pederson and Thomsen, 2000 and Thomsen and Pederson, 2003). In emerging economies, owner identity is more important than ownership concentration (Dyck, 2000;Firth et al 2007;Omran et al 2008;Wu et al 2009 andChi and).…”
Section: Divc= Votr1 -Casr1mentioning
confidence: 95%
“…Researcher showed that the level of executive compensation mainly depends on company properties as well as on personal characteristics of the manager. Firm size (Fahlenbrach 2009;Renner et al 2002) firm performance (Antle and Smith 1986;Bebchuk and Fried 2006;Devers et al 2007), and a firm's ownership structure (Thomsen and Pedersen 2000;Chowdhury and Wang 2009) are company properties that researchers identified as drivers of executive compensation levels. Managers' tenure (Hill and Phan 1991) and gender (Kulich et al 2011;Renner et al 2002), on the other hand, are personal characteristics that influence managers' compensation levels directly or as moderating effects, e.g., through affecting labor market mobility and search firms' preferences (Dreher et al 2011).…”
Section: Literature Overview Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The ownership structure (Thomsen and Pedersen 2000;Chowdhury and Wang 2009) is represented by the two dummy variables EXTERNAL_BLOCKHOLDER and OWNER_CONTROLLED_MANAGING_BOARD. We also control for the following board characteristics expecting a lower compensation with more efficient boards: #COMMITTEES measures the number of committees composed by the board and might decrease control efficiency of the board since decisions can be made in small groups and do not necessarily have to be defended in front of all board members.…”
Section: Variablesmentioning
confidence: 99%
“…According to Thomsen and Pedersen (2000), ownership has at least two (2) dimensions. First, is the identity and concentration of ownership and secondly, the legal status of the contract which regulates the ownership.…”
Section: Majority Shareholdermentioning
confidence: 99%